The Utilization of Household Waste in the Development of Organic Agriculture to Realize a Green Economy - Triono, Bambang; Irvan Nur Ridho; Etica, Use Etica; Anindya Dewi Aureailona; Zafira Azalia Rakhma Affandy (Edumedia Solution, 2025)
The Community Partnership Program (PKM) was implemented to promote the realization of a green economy through the utilization of household waste as raw material for organic agriculture. The program’s partner is Jamaah Tani Muhammadiyah (JATAM), a local community group focused on sustainable farming. The activities began with training on organizational management and product management to strengthen internal capacity, followed by technical training on the use of waste-sorting equipment. The results of the program indicate an improvement in organizational capacity, particularly in task delegation, program coordination, and institutional strengthening. In addition, the organization’s output orientation became more explicit with the introduction of waste processing into economically valuable products such as compost and liquid organic fertilizer (POC). These products not only serve as inputs for organic agriculture but also carry market potential as a source of sustainable funding. Conceptually, the program integrates the principles of circular economy and sustainability, framing waste as a valuable resource. In this way, the PKM contributes on two fronts: strengthening JATAM’s institutional capacity while simultaneously creating an organic farming ecosystem that supports the green economy.